The impact of digital comics on a group of university students - Moncayo Herrera, Enrique; Camacho Castillo , Luis Alfredo; Sánchez Palma, Lady Denisse (Research, Society and Development, 2025)
Motivating English as a Foreign Language (EFL) learners in online classes can be a significant challenge. This study aims to evaluate students' engagement and improvement in English skills through the use of digital comics as a primary learning tool. To address the research questions, the author employed observational techniques over several weeks and administered an exploratory questionnaire to gather students' experiences with digital comics. The findings reveal that 80% of the students had used digital comics for the first time to learn a second language, with 59 out of 67 students expressing engagement with the medium. Additionally, 61 students reported that incorporating sound and imagination into story creation inspired them to learn English. Overall, the study suggests that digital comics had a positive impact on student engagement and learning. However, it also highlights the challenges faced by educators, particularly the lack of technological resources in many Ecuadorian institutions, which limits the full potential of this tool in language instruction.